A QE Study on Golf Putting - Seok-hyun Song; Dong-Wook Han (Korea Institute of Sport Science, 2022)
PURPOSE The quiet eye (QE) is defined as the final fixation time that is a specific target prior to initiating movement. This study aimed to identify the cause of QE in golf putting and to present an efficient practice method for improving putting skills. METHODS Thirty participants were randomly assigned to one of three groups. Each group practiced golf putting in different ways for two days. RESULTS The QE group showed a significant difference in putting scores, which was higher than that of the control group. The visual-occlusion group showed no difference compared to the other groups in terms of putting scores. The QE group showed a significant difference in terms of QE in the retention and competition tests compared to the pretest. The control group tended to have a slightly longer QE in competition tests compared to the pretest. The visualocclusion group showed no statistically significant difference in QE based on the period. All three groups had significantly longer swing times over the selected period. There was no significant difference in terms of the alpha power of the occipital lobe based on group and period. CONCLUSIONS The position of the visual-occlusion group became stable. However, the QE did not lengthen. The QE group had a longer QE. Furthermore, the control group that practiced with their eyes open tended to have longer QE. Therefore, QE may be related to visual-based cognitive processing rather than posturalkinematics. Finally, this study proved that QE practice is a more efficient method for novices in golf putting.